OpenStudy (anonymous):

Which of the following tables shows the correct steps to transform x^2 + 4x + 3 = 0 into the form (x - p)^2 = q? [p and q are integers] Step 1 x^2 + 4x + 3 + 1 = 0 + 1 Step 2 x^2 + 4x + 4 = 1 Step 3 (x + 2)^2 = 1 Step 1 x^2 + 4x + 3 - 1 = 0 - 1 Step 2 x^2 + 4x + 2 = -1 Step 3 (x + 2)^2 = -1 Step 1 x^2 + 4x + 3 - 2 = 0 - 2 Step 2 x^2 + 4x + 1 = -2 Step 3 (x + 2)^2 = -2 Step 1 x^2 + 4x + 3 + 2 = 0 + 2 Step 2 x^2 + 4x + 5 = 2 Step 3 (x + 2)^2 = 2

3 years ago
OpenStudy (anonymous):

@dan815 @AquaStone316 @iGreen

3 years ago
OpenStudy (anonymous):

I believe that it is the 1st answer. I'm not entirely sure as I haven't done this in a little while.

3 years ago
OpenStudy (anonymous):

I don't know. I suck badly at Math.

3 years ago
OpenStudy (anonymous):

@iambatman @amistre64

3 years ago
OpenStudy (amistre64):

how do you normally complete a square?

3 years ago
OpenStudy (amistre64):

to dbl chk ... what does (x+2)^2 expand to?

3 years ago
OpenStudy (anonymous):

|dw:1430511023614:dw|

3 years ago
OpenStudy (amistre64):

then that should be evidence enough for the first option

3 years ago
OpenStudy (anonymous):

Thank you.

3 years ago
OpenStudy (amistre64):

youre welcome

3 years ago